Financial Literacy Counseling: Avoiding Fictitious Investments for Teachers and Parents at Taman Indria Kindergarten, Bandung City - Fakhri, Mahendra; Wardhana, Aditya (Journal of Community Service and Society Empowerment, 2024)
The level of financial literacy of Indonesian people is currently showing an encouraging increase, in 2023 the level of financial literacy of Indonesian people will reach 69.7 points, an increase from 2020 of 66.5 points, this means that the level of knowledge and understanding of Indonesian people towards money is in a good position. which is encouraging. This can be seen from the increase in activities in the financial sector, such as now every person has a bank account, which means that every citizen in Indonesia has started to understand about saving, apart from that, Generation Z has now started talking about investment, especially stock investment, this Of course it is encouraging because the literacy skills of Indonesian citizens can be equated with those of other developed countries. The increase in the financial literacy index has of course been encouraging lately, but there are still incidents reported by both the media and social media regarding victims of fraudulent investments. Bodong investment is a term for fraudulent activities under the guise of investment. This usually happens when a party offers an investment with a high rate of return, without risk, which makes people tempted and even decide to follow the investment. In the name of investment, these fraudulent activities never seem to disappear in Indonesia, as if people have never learned from previous experiences. This can happen because even though the level of financial literacy has increased, if someone carries out their activities, their finances are not only always influenced by a high level of intelligence, but they are also affected. by psychological factors, so it is natural that fraudulent investment incidents always occur. This community service activity takes the form of outreach and community outreach to the target community which is divided into two stages. The first stage, planning between the organizer and the target community begins with completing an administrative recommendation form and a letter of willingness for the target which contains roles, duties, principal and functions. The second stage, implementation takes the form of counseling delivered offline (outside the network) taking place in the school hall. This community service activity is actually a form of plan in the form of a digital financial counseling series. So the relevance of one activity to other activities will be designed. Thus, it is still open for the next series of service with coverage not only of the same target community but also the network of the target community itself, in this case the community and other community institutions that are part of the Taman Indria Kindergarten network (parent to Taman Siswa) around the city of Bandung, so that The digital financial literacy target could be more broadly segmented.